2020
DOI: 10.1038/s41598-020-79149-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving climate suitability for Bemisia tabaci in East Africa is correlated with increased prevalence of whiteflies and cassava diseases

Abstract: Projected climate changes are thought to promote emerging infectious diseases, though to date, evidence linking climate changes and such diseases in plants has not been available. Cassava is perhaps the most important crop in Africa for smallholder farmers. Since the late 1990’s there have been reports from East and Central Africa of pandemics of begomoviruses in cassava linked to high abundances of whitefly species within the Bemisia tabaci complex. We used CLIMEX, a process-oriented climatic niche model, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 89 publications
3
70
0
Order By: Relevance
“…Instead of using plant hardiness zones, other approaches may be more accurate and, therefore, informative. For example, CLIMEX or Maxent species distribution modeling may prove useful as more worldwide occurrence data and documented physiological tolerances become available ( Kriticos et al 2015 , Kumar et al 2016 , Zhu et al 2020 ). Accordingly, more detailed research regarding the ecological relationships and life cycle of V. mandarinia in the Pacific Northwest needs to be undertaken to form a more complete picture of what can actually be defined as suitable habitat within this region.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Instead of using plant hardiness zones, other approaches may be more accurate and, therefore, informative. For example, CLIMEX or Maxent species distribution modeling may prove useful as more worldwide occurrence data and documented physiological tolerances become available ( Kriticos et al 2015 , Kumar et al 2016 , Zhu et al 2020 ). Accordingly, more detailed research regarding the ecological relationships and life cycle of V. mandarinia in the Pacific Northwest needs to be undertaken to form a more complete picture of what can actually be defined as suitable habitat within this region.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Several factors have been attributed to the emergence and successful establishment of plant viruses in a wide array of agricultural systems. These include: extensive monoculture of crops that are susceptible to both viruses and vectors, the movement of virus-infected plant materials and insect vectors from their native to new environments, plant viruses’ ability to rapidly evolve and adapt, and the effect of climate change on the distribution area of hosts and vectors [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Many plant viruses also possess a broad host range, which in turn aids in their successful establishment in new environments [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the East African region, Kriticos et al (2020) demonstrated a clear correlation between cassava mosaic disease proliferation and a 39 year change in environmental suitability for a B. tabaci whitefly species. The species in question, Middle East‐Asia Minor 1, has not been recorded as a pest of cassava (Kriticos et al, 2020). Assuming B. tabaci species SSA1–SSA5 are subject to similar environmental trends, we separate out several ways in which invasion of severe CMD may have been influenced by the changing environment.…”
Section: Discussionmentioning
confidence: 99%